Web Based Cash Flow Information System - Heldalina; Fitria; Muhammad Syahid Pebriadi; Putriana Salman; Anhar Khalid (MultiTech Publisher, 2023)
This study aims to find out the right Cash Management Accounting Information System for Rezeky sources and to produce a Cash Flow Information System, namely Web-Based Cash Receipts and Cash Disbursements. The theoretical framework is to analyze the Cash Management Accounting Information System by analyzing the information needed by management, related functions, a network of procedures, accounting documents and records used, flowcharts, and the current internal control system. The developed application program is the first step, which is carried out by designing relationships between tables, interfaces, and outputs. This study found that all daily cash records at Sumber Rezeky still use financial report books and notes. The author suggests using a web-based cash receipt and cash disbursement application to help Sumber Rezeky record customer data, record cash management transactions, and make it easier to find information on cash receipts and disbursement transactions.